Endophthalmitis with opaque cornea managed with primary endoscopic vitrectomy and secondary keratoplasty: Presentations and outcomes - Vivek P Dave (Indian Journal of Ophthalmology, 2020)
Purpose: To describe the outcomes of endophthalmitis with opaque cornea managed with primary endoscopic vitrectomy and secondary keratoplasty. Methods: Retrospective consecutive interventional case series. All cases of endophthalmitis with opaque cornea which underwent endoscopic vitrectomy followed by secondary keratoplasty were analyzed. The study period was from Jan 2015 to March 2019. The outcome measures were resolution of infection, the magnitude of unnecessary keratoplasties avoided and corneal graft survival. The final anatomic and functional outcomes were reported and compared with relevant literature. Results: Seventy-eight eyes of 78 patients underwent endoscopic pars plana vitrectomy for endophthalmitis with the opaque cornea, of these 14 eyes of 14 patients were deemed eligible for further corneal intervention and were included in the study. The mean age at presentation was 42.27 ± 21.6 years (median 36 years). Etiology-wise, eight cases (57.14%) were post-trauma, three cases (21.42%) post-keratoplasty, two cases (14.28%) were endogenous, and one case (7.14%) following corneal dermoid excision and wound melt. Culture positivity was in 5/14 (35.71%). The mean interval between endoscopic vitrectomy and keratoplasty was 5.42 ± 2.69 months (median 3.5 months). The mean follow-up noted was 20.42 ± 11.45 months (median 17.5 months). The infection resolved in 100% of cases. Unnecessary keratoplasties were avoided in 64/78 (82%) cases due to the primary endoscopic intervention. The favorable anatomic outcome was seen in 11/14 (78.57%) of cases and favorable functional outcome in 8/14 (57.14%) cases. Conclusion: Endoscopic vitrectomy allows for early intervention in endophthalmitis with the opaque cornea. This facilitates early settlement of infection, globe preservation, greater graft survival, and lesser repeat posterior segment procedures.